ChemInform Abstract: Single and Multiple Peptide γ‐Turns: Literature Survey and Recent Progress. Issue 28 (July 2015) - Crisma, Marco; De Zotti, Marta; Moretto, Alessandro; Peggion, Cristina; Drouillat, Bruno; Wright, Karen; Couty, Francois; Toniolo, Claudio; Formaggio, Fernando
Abstract Review: 102 refs.